Co3O4@CoNi-LDH core/shell nanosheet arrays for high-performance battery-type supercapacitors - Zhou, Jiao-Jiao; Li, Qin; Chen, Chen; Li, Yan-Li; Tao, Kai; Han, Lei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
Co3O4@CoNi-LDH core/shell nanosheet array on Ni foam was prepared as an integrated battery-type electrode for supercapacitors and exhibits high specific capacitance and excellent cycling stability. [Display omitted] •Co3O4@CoNi-LDH core/shell nanosheet array on Ni foam was prepared.•The composite material exhibits high specific capacitance and excellent cycling stability.•The assembled asymmetric supercapacitor device exhibits high energy density.•The red light-emitting diode (LED) can be illuminated by two connected ASCs. Co3O4@CoNi-layered double hydroxide (LDH) core/shell nanosheet array on Ni foam was prepared as an integrated battery-type electrode for supercapacitors by growth of CoNi-LDH nanosheets shell on the surface of Co3O4 plates core. The resulting composite material exhibits high specific capacitance (2676.9 F g−1 at 0.5 A g−1) and excellent cycling stability. The improved electrochemical behavior is benefited from the typical mesoporous structure, which shorten the diffusion distance of OH− in the electrolyte and the strong core/shell binding interaction among Co3O4 and CoNi-LDH nanosheet arrays. Additionally, an assembled asymmetric supercapacitor (ASCs) device using as-fabricated Co3O4@CoNi-LDH as positive electrode and activated carbon (AC) as negative electrode also exhibits a high energy density of 61.23 Wh kg−1 at a high power density of 750 W kg−1, furthermore, still remains 24.8 Wh kg−1 even at a higher power density of 7500 W kg−1. Most importantly, a red light-emitting diode (LED) can be illuminated by two connected ASCs, indicating that as-synthesized Co3O4@CoNi-LDH possesses great potential for practical applications. As a result, this work demonstrates a feasible strategy for the design and fabrication of metal oxides/LDH composites for applications in energy storage systems.